Improving the system and methods of teaching the Russian language for physicians - Abdullaeva Rozanna Mirzatullaevna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article discusses various forms of conducting classes in the Russian language. In the current educational system, the use of various innovative forms of teaching is a necessary condition for the professionalism of a teacher.